2011
DOI: 10.1017/s1355617711001731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marathi-Hindi Bilingualism on Neuropsychological Performance

Abstract: The present study aimed to examine if bilingualism affects executive functions and verbal fluency in Marathi and Hindi, two major languages in India, with a considerable cognate (e.g., activity is actividad in Spanish) overlap. A total of 174 native Marathi speakers from Pune, India, with varying levels of Hindi proficiency were administered tests of executive functioning and verbal performance in Marathi. A bilingualism index was generated using self-reported Hindi and Marathi proficiency. After controlling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The nature of the bilingual pairing of Welsh/English may affect the nature of the interaction with neuropsychological function and language as it has done in other language pairs [ 27 ]. This is the first study of cognitive reserve in any neurodegenerative condition in Welsh/English bilinguals and the effect has not yet been demonstrated in this population for AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of the bilingual pairing of Welsh/English may affect the nature of the interaction with neuropsychological function and language as it has done in other language pairs [ 27 ]. This is the first study of cognitive reserve in any neurodegenerative condition in Welsh/English bilinguals and the effect has not yet been demonstrated in this population for AD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study there was a significant correlation between the degree of bilingualism and one test of nonverbal general reasoning and one of working memory although there was no correlation with any other test of executive function. The effects of the degree of bilingualism may warrant further study since the nature of the different bilingual pairs and degree of switching between the languages may influence the effect of cognitive reserve [ 27 ]. In the present study there was no effect of a greater daily use of Welsh on EF although there was an effect on a test of vocabulary favouring those who used less Welsh in daily life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this test battery was sensitive to relatively mild, HIV-associated neurocognitive disorders (HAND) in previous studies conducted in China (Cysique et al, 2010; Heaton et al, 2008; Schrier et al, 2012; Spector et al, 2010), and in numerous other non-Western countries including Zambia (Hestad et al, 2012), Cameroon (Kanmogne et al, 2010; Njamnshi et al, 2009), Nigeria (e.g., Royal et al, 2012), South Africa (Spies et al, 2012), India (Kamat et al, 2012), Romania (Joseph et al, 2013), and Brazil (Ellis et al, 2007), in addition to the U.S. (e.g., Heaton et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to expectations, we found that HIV+ patients performed better on demographically-corrected measures of verbal fluency compared to HIV− controls. This unexpected result raises the possibility that the normative corrections, developed from a relatively small, HIV−, control group, inadequately controlled for the effects of factors such as bilingualism and quality of education, which might impact performance on language measures 30 . This study was not designed to capture these variables.…”
Section: Discussionmentioning
confidence: 99%